How do Investors React Differently? Dynamic Analysis of Investor Ownership Movement: Evidence from Indonesia Listed Company - Ngangi, Syeren Amanda; Kwee, Yohanis Hans (Journal of Management and Business Review, 2025)
This study aims to dynamically analyze how global macroeconomic, domestic macroeconomic, and microeconomic variables influence the movements of foreign institutional, domestic institutional, and retail investors in Company X. The analysis utilizes monthly secondary data from September 2019 to October 2024, processed using the Vector Error Correction (VEC) model. The variance decomposition result show that the exchange rate is the most significant long-term across investor types. In the short term, the remaining variables affect each investor group differently: (i) GDP primarily impacts foreign institutional investors; (ii) P/E affects both domestic institutional and retail investors. The impulse response function indicates that exchange rate shocks have the greatest influence on investors. The Granger causality test shows significant effects from: (i) exchange rate and GDP to foreign institutional investors, (ii) the exchange rate to domestic institutional investors, and (iii) the Fed rate to retail investors. These findings contribute to the understanding of investor behavior and offer practical insights for developing investor relations strategies for company X.